A Descriptive Case Study: Challenges experienced by health care workers (HCW) at a primary health care facility when serving deaf/hearing impaired (HI) patients - Orrie, Shameela (Department of Public Health and Family Medicine, 2022)
Introduction Deaf people experience significant barriers in access to health care as well as poorer health outcomes. While there are many international and South African studies describing the difficulties deaf patients experience when accessing health care, only anecdotal evidence suggests that health care workers (HCW) also experience challenges at these encounters. These difficulties are significant as they may results in errors in medical management with significant impact on mortality and morbidity of the patient as well impacting on future encounters. This study was intended to further the understanding of the dynamics of the encounters between HCW and deaf patient by examining the HCWs experience. In this way we may identify the intrinsic and extrinsic factors contributing to the success of failure of the task, establish if the HCW has the competencies and training to achieve the objectives, how working conditions impact on success and how HCWs adapt their communication strategies. These findings could advocate for changes to formal training HCWs receive and the planning and adaptation of services offered to give deaf patients access to appropriate and effective health care. Methods The study design is a qualitative, descriptive case study. Data was collected using interviews and focus groups of invited staff members at Retreat Community Health Centre (RCHC) in Cape Town. Convenience sampling was used to select participants, and interviews were conducted until saturation was reached. Data was studied and analysed using the phenomenological method. Results HCWs reported that they serve very few Deaf or HI clients. However, themes of language barriers; resilience; preconceptions; improvisation and innovation: interpreters and recommendations emerged. Difficulties in communication were acknowledged, but HCWs insisted that these barriers are not insurmountable. Discussion and conclusion A few preconceptions and gaps in knowledge and awareness were revealed. HCWs also tended to rely on escorts and other interpreters. The dominant recommendations are that HCWs should receive training in sign language (SL) and/or that SL Interpreters be available at facilities. Despite using words and phrases such as “frustrating” and “more effort”, participants concluding remarks reiterate that their experiences are positive, suggesting a notable resilience.